6q+3q-q=24findq

Simple and best practice solution for 6q+3q-q=24findq equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6q+3q-q=24findq equation:


Simplifying
6q + 3q + -1q = 24findq

Combine like terms: 6q + 3q = 9q
9q + -1q = 24findq

Combine like terms: 9q + -1q = 8q
8q = 24findq

Solving
8q = 24dfinq

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-24dfinq' to each side of the equation.
-24dfinq + 8q = 24dfinq + -24dfinq

Combine like terms: 24dfinq + -24dfinq = 0
-24dfinq + 8q = 0

Factor out the Greatest Common Factor (GCF), '8q'.
8q(-3dfin + 1) = 0

Ignore the factor 8.

Subproblem 1

Set the factor 'q' equal to zero and attempt to solve: Simplifying q = 0 Solving q = 0 Move all terms containing q to the left, all other terms to the right. Simplifying q = 0

Subproblem 2

Set the factor '(-3dfin + 1)' equal to zero and attempt to solve: Simplifying -3dfin + 1 = 0 Reorder the terms: 1 + -3dfin = 0 Solving 1 + -3dfin = 0 Move all terms containing q to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3dfin = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3dfin = 0 + -1 -3dfin = 0 + -1 Combine like terms: 0 + -1 = -1 -3dfin = -1 Add '3dfin' to each side of the equation. -3dfin + 3dfin = -1 + 3dfin Combine like terms: -3dfin + 3dfin = 0 0 = -1 + 3dfin Simplifying 0 = -1 + 3dfin The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

q = {0}

See similar equations:

| 90x+x=90 | | 8x+4y=10y | | 6x-2=-4c+8x | | 180x+x=180 | | 2(2-x)=8-2(2-x) | | f(x)=(15x) | | y+16=20 | | 90x+x=180 | | 10-.25x=.5+4 | | 4(v+5)+8v=32 | | x^2-10x-27=0 | | x-76y=0 | | 12x^2+6x+82=0 | | 4x^2-5sinx=0 | | -5n-3n+2=34 | | 18x-6=-10 | | 4x^2-5sinx= | | (6+u)(3u+4)=0 | | (27x)27=21(21+2x+8) | | 2(2-x)=8-2(-x) | | ln(6)+ln(x)=4 | | 2x+3(2+5)=X | | 4(3x^2+2x)-12x^2=2(8x+6) | | 4x+3(x-6)=-11 | | -6-(21-6X)=-51+2X | | 4x-9y+6x+3y-2x=0 | | 3(2x-6)-(2x+1)=9 | | 2x+1=3(x-1) | | 5x-3x=x+9 | | 8n=5n+39 | | 7.4=w-3.9 | | 33=7(w+7)-3w |

Equations solver categories